2011
DOI: 10.1371/journal.pone.0017413
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Seasonality: Complex Demodulation as a Novel Approach in Epidemiologic Analysis

Abstract: BackgroundSeasonality of suicides is well-known and nearly ubiquitous, but recent evidence showed inconsistent patterns of decreasing or increasing seasonality in different countries. Furthermore, strength of seasonality was hypothesized to be associated with suicide prevalence. This study aimed at pointing out methodological difficulties in examining changes in suicide seasonality.Methododology/Principal FindingsThe present study examines the hypothesis of decreasing seasonality with a superior method that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(64 reference statements)
1
13
0
1
Order By: Relevance
“…Goodwin and Jamison [7] reviewed 61 studies in the northern hemisphere and found a striking May peak in suicides and a less common, smaller bimodal October peak. Since the review of Goodwin and Jamison [7], there have been dozens of additional studies that have replicated consistent late spring peaks in suicide in nearly all of the largest datasets, including in the northern hemisphere (in those studies that reported both a monthly peak and a total n for suicides), the USA (May; n = 649,843, the present study), Japan (April; n = 501,950 [29]), Sweden (May; n = 161,182 [30]), Italy (May; n = 141,180 [31]), Finland (May; n = 96,159 [30]), England (January; n = 92,909 [32]), Austria (May; n = 67,741 [33]), Mexico (May; n = 64,298 [34]), Spain (July; n = 42,905 [35]), Denmark (May; n = 37,987 [36]), Switzerland (May/June; n = 37,518 [37]), Norway (May; n = 20,156 [38]), China (May; n = 14,450 [39]), and Ireland (April; n = 7,899 [40]). In the southern hemisphere, reciprocal spring peaks have been found in Australia (November; n = 57,936 [41]), South Africa (October; n = 16,389 [42]), and São Paulo, Brazil (November; n = 6,916 [43]).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Goodwin and Jamison [7] reviewed 61 studies in the northern hemisphere and found a striking May peak in suicides and a less common, smaller bimodal October peak. Since the review of Goodwin and Jamison [7], there have been dozens of additional studies that have replicated consistent late spring peaks in suicide in nearly all of the largest datasets, including in the northern hemisphere (in those studies that reported both a monthly peak and a total n for suicides), the USA (May; n = 649,843, the present study), Japan (April; n = 501,950 [29]), Sweden (May; n = 161,182 [30]), Italy (May; n = 141,180 [31]), Finland (May; n = 96,159 [30]), England (January; n = 92,909 [32]), Austria (May; n = 67,741 [33]), Mexico (May; n = 64,298 [34]), Spain (July; n = 42,905 [35]), Denmark (May; n = 37,987 [36]), Switzerland (May/June; n = 37,518 [37]), Norway (May; n = 20,156 [38]), China (May; n = 14,450 [39]), and Ireland (April; n = 7,899 [40]). In the southern hemisphere, reciprocal spring peaks have been found in Australia (November; n = 57,936 [41]), South Africa (October; n = 16,389 [42]), and São Paulo, Brazil (November; n = 6,916 [43]).…”
Section: Discussionmentioning
confidence: 84%
“…Statistically significant increases in the amplitude of the seasonal suicide rhythm have also been found in Ireland (1980–2000) [40] and Australia (1970–1999) [41]. By contrast, the amplitude of the seasonal suicide rhythm did not change significantly in either Austria (1970–2008) [33] or China (1991–2009) [39], whereas in Norway (1969–2007) [38] and possibly Slovenia (1971–2002) [45] the amplitude decreased significantly. Clearly, the factors that contribute to these disparate temporal variations in the amplitude of the seasonal suicide risk factor are of great interest [8].…”
Section: Discussionmentioning
confidence: 99%
“…This analytical technique can improve the characterization of the seasonality of suicide as well as increase knowledge about the processes leading up to it and the potential influences of temporary exogenous changes. While this technique has been used in other countries to analyze suicides [ 25 ], this is the first investigation of this type in Mexico. Therefore, the aim of the present analysis is to explore the seasonal behavior of suicide in Mexico using spectral decompensation and extensively characterize all the cases occurring at the national level between the years 2000 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Es scheint plausibel, dass die niedrigere saisonale Variabilität der Suizidmortalität im Norden Chiles auch dem bekannten stimmungsstabilisierenden und antisuizidalen Effekt von Lithium geschuldet sein könnte [16]. Allerdings muss in Betracht gezogen werden, dass die Amplituden suizidaler Saisonalität in Regionen mit niedrigen Suizidraten aus statistischen Gründen eher gering sind -wie schon in der Literatur beschrieben [34].…”
Section: Diskussionunclassified